Personality and Students’ Knowledge about Ecosystem Related to Environmental Behavior of Grade XI Senior High School Students at SMA N 112, West Jakarta - Agus Ramdani (IJEEM - Indonesian Journal of Environmental Education and Management, 2018)
The objective of this research is to find out the effect of Personality (P) and knowledge students about ecosystem (KS) on environmental behaviour (EB). An expost facto method has been used by selecting 8 sample for each cell. Reliability of P was .964, KS was .937 and EB was .95. Data analyzed by two-way ANOVA. Research results revealed that there was environmental behaviour significant difference between those students who have most extraversion personality compared to introversion personality. Moreover, there was significant interaction effect between personality and knowledge students about ecosystem on environmental behaviour.